Patient-derived organoids of lung cancer based on organoids-on-a-chip: enhancing clinical and translational applications - Zeng, Xiao; Ma, Qiong; Li, Xue-Ke; You, Li-Ting; Li, Jia; Fu, Xi; You, Feng-Ming; Ren, Yi-Feng (Frontiers in Bioengineering and Biotechnology, 2023)
Lung cancer is the one of the most common malignant tumors worldwide, with high morbidity and mortality due to significant individual characteristics and genetic heterogeneity. Personalized treatment is necessary to improve the overall survival rate of the patients. In recent years, the development of patient-derived organoids (PDOs) enables lung cancer diseases to be simulated in the real world, and closely reflects the pathophysiological characteristics of natural tumor occurrence and metastasis, highlighting their great potential in biomedical applications, translational medicine and personalized treatment. However, the inherent defects of traditional organoids, such as poor stability, the tumor microenvironment with simple components and low throughput, limit their further clinical transformation and applications. In this review, we summarized the developments and applications of patient-derived lung cancer organoids and discussed the limitations of traditional PDOs in clinical transformation. Herein, we looked into the future and proposed that organoids-on-a-chip based on microfluidic technology are an advantageous model for personalized drug screening. In addition, combined with recent advances in lung cancer research, we explored the translational value and future development direction of organoids-on-a-chip in the precision treatment of lung cancer.